2012
DOI: 10.1159/000338785
|View full text |Cite
|
Sign up to set email alerts
|

Osteocalcin, Cortisol Levels, and Bone Mineral Density in Prepubertal Children with Asthma Treated with Long-Term Fluticasone Propionate

Abstract: Aims: The objective of this study is to determine the effects of the long-term treatment with inhaled fluticasone propionate on osteocalcin, cortisol levels, and bone mineral status in children with asthma. Methods: This cross-sectional study examined 230 prepubertal children with asthma (aged 6–11) who had intermittently used inhaled fluticasone propionate for at least 5 years at a mean daily dose of 200 µg (range: 200–350 µg). Serum osteocalcin, cortisol, and bone mineral density (BMD) of the lumbar spine we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 56 publications
0
6
2
Order By: Relevance
“…The authors concluded that changes in BMD interact with changes in height, which means that monitoring children's heights gives an approximation of the effects of ICS on bone . The most recent cross‐sectional study including retrospective follow‐up time did not find a difference in lumbar BMD in pre‐pubertal children using intermitted fluticasone with 200 µg mean daily dose for 5 years compared with newly diagnosed asthmatic children with no history of ICS medication …”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…The authors concluded that changes in BMD interact with changes in height, which means that monitoring children's heights gives an approximation of the effects of ICS on bone . The most recent cross‐sectional study including retrospective follow‐up time did not find a difference in lumbar BMD in pre‐pubertal children using intermitted fluticasone with 200 µg mean daily dose for 5 years compared with newly diagnosed asthmatic children with no history of ICS medication …”
Section: Discussioncontrasting
confidence: 64%
“…28 The most recent crosssectional study including retrospective follow-up time did not find a difference in lumbar BMD in pre-pubertal children using intermitted fluticasone with 200 mg mean daily dose for 5 years compared with newly diagnosed asthmatic children with no history of ICS medication. 29 Due to the long follow-up time, the median cumulative ICS dose in the present study was higher than in two previous French and Finnish studies. 3,28 In the CAMP study, Danish study and recent Turkish study the ICS dose was higher than the median dose of this study.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In another study, the skeletal status in children with asthma using inhaled fluticasone propionate was assessed by bone mineral density measurement at the lumbar spine and some biochemical markers (osteocalcin and cortisol). 35 Comparisons with healthy controls revealed no significant differences in the analyzed parameters. The same group of authors confirmed later their conclusion about the lack of a negative impact of inhaled glucocorticosteroids on dual-energy x-ray absorptiometric results for the lumbar spine in a larger cohort of asthmatic children.…”
Section: Discussionmentioning
confidence: 87%
“…Picard et al evaluated the impact of inhaled glucocorticosteroids on the SoS measured at the tibia in 85 children with mild‐to‐moderate asthma and found no deleterious effect of the therapy. In another study, the skeletal status in children with asthma using inhaled fluticasone propionate was assessed by bone mineral density measurement at the lumbar spine and some biochemical markers (osteocalcin and cortisol) . Comparisons with healthy controls revealed no significant differences in the analyzed parameters.…”
Section: Discussionmentioning
confidence: 99%